IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Hayati, Zuqriva; lian Ikhsan; Iswantir; Fauzan Azim (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2024)
This paper aims to discuss the implementation of the free curriculum of learning in the subject of Islamic Religious Education in SMAN 1 Bukittinggi. Therefore the location in this study was SMA Negeri 1 Bukittinggi. This type of research is descriptive qualitative using a field study approach. Data collection methods by means of observation and in -depth interviews conducted by the author of research information. Furthermore, the data obtained is analyzed with three stages namely, data reduction, data display, and drawing conclusions. The results showed that SMA Negeri 1 Bukittinggi had implemented an independent curriculum learning independently in 2022/2023 including the subjects of Islamic Religious Education. Learning Islamic Religious Education consists of regular learning (intracuricular) carried out using a learning approach that is centered on students and perfected with the Pancasila Student Profile Project (Kokuricular). Implementation of the Merdeka Curriculum Learning at SMAN 1 Bukittinggi certainly does not stop to the independent stage changes, but will also increase by implementing the Mandiri Sharing curriculum.